2018
DOI: 10.1039/c8ra01916a
|View full text |Cite
|
Sign up to set email alerts
|

Partially reduced graphene oxide and chitosan nanohybrid membranes for selective retention of divalent cations

Abstract: Partially reduced graphene oxide and chitosan nanohybrid membranes were fabricated to exhibit selective retention of divalent cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Chitosan is a natural polymer derived from the deacetylation of chitin, and is considered the second most common natural polysaccharide. [1][2][3] Due to its low cost, easy lm-forming capacity, environmental friendliness, alkali stability, biodegradability, excellent mechanical properties and thermal stability, it is very valuable in the preparation of membranes, and has attracted great research interest. [4][5][6][7] Many studies have reported that chitosan has an excellent ability to form microspheres, membranes and bers, which gives it a signicant advantage over other absorbable membrane materials in the design of packaging structures.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a natural polymer derived from the deacetylation of chitin, and is considered the second most common natural polysaccharide. [1][2][3] Due to its low cost, easy lm-forming capacity, environmental friendliness, alkali stability, biodegradability, excellent mechanical properties and thermal stability, it is very valuable in the preparation of membranes, and has attracted great research interest. [4][5][6][7] Many studies have reported that chitosan has an excellent ability to form microspheres, membranes and bers, which gives it a signicant advantage over other absorbable membrane materials in the design of packaging structures.…”
Section: Introductionmentioning
confidence: 99%
“…The intense peak at a 230 nm wavelength is the characteristic peak of GO, which is related to the π–π* transition of C=C [ 28 ]. The small shoulder at a 304 nm wavelength relates to the n–π* transition of C=O [ 29 ]. After the addition of CMC, the peak at 230 nm shifted to 260 nm, suggesting the successful reduction of GO.…”
Section: Resultsmentioning
confidence: 99%
“…47 To achieve selective retention of divalent cations, a reduced GO and nanohybrid membrane was developed. 48 A new method for synthesizing composites by direct chemical exfoliation of graphite and CHI dissolved in acetic or aspartic acid was reported. 49…”
Section: Introductionmentioning
confidence: 99%